Peningkatan Literasi & Numerasi Anak Melalui Program Belajar Berbasis Alam Didesa Namo Suro Baru - Febrina S.L. Lumbantobing; Sonya Hutabarat; Atika Suriani Laia; Yufiriani Lase (Lembaga Pengembangan Kinerja Dosen, 2025)
Community service activities are one of the compulsory courses to train students to establish the knowledge and skills they have in a learning process according to their respective fields of study. The purpose of the mini PkM is to improve children's literacy and numeracy skills in Namo Suro Baru Village, Sibiru-Biru District, Deli Serdang Regency, by using a more contextual and applicable nature-based learning approach, encouraging children to be more active and creative in the learning process through direct experience in nature, so that they can understand and apply the concept of literacy and numeracy in their daily lives, increase children's concern for their environment, through learning that utilizes nature as a learning medium, and introduces them to the importance of biodiversity and good environmental management. So that the results of this PkM are that children show an increase in reading simple words and sentences. They also began to be able to write basic words better. Children who were initially only able to count numbers in a limited way, are now able to do simple calculations faster and more accurately. Activities carried out outdoors make children more active and enthusiastic in learning. Keywords: Numeracy, Literacy, Natural Environment.